Building better. Sustainable architecture for family homes. - (:unkn) unknown (Gestalten Verl., 2014)
Sustainability and energy efficiency play a critical role for anyone building or renovating a house. Thankfully, architects from around the world are now developing single-family homes that combine ecological responsibility with contemporary and imaginative design. Building Better is an engaging visual showcase of outstanding environmentally friendly houses. It not only offers an insightful exploration of the latest developments in sustainable design, but it also takes an in-depth look at the high performance building materials and technical data involved in each featured project. In the book, architects and homeowners work together to find unique and aesthetically compelling ways to build more sustainably. Melding client desires with real world pragmatism, these efficient homes present a diverse spectrum of solutions that include everything from state of the art climate control systems to ancient, passive, and renewable building techniques.
Keywords: Bebauung; Wohngebäude; Einfamilienhaus; Architektur; Baumaterial; Ökologisches Bauen; Umweltverträglichkeit; Beispielsammlung; Bildband; Erneuerbare Energie